2021
DOI: 10.1590/s0004-2803.202100000-23
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Lymphocyte Ratio Predicts Short-Term Mortality in Patients Hospitalized for Acute Decompensation of Cirrhosis

Abstract: BACKGROUND: Individuals with cirrhosis have a chronic systemic inflammation associated with an immune dysfunction, affecting the progression of the liver disease. The neutrophil-lymphocyte ratio (NLR) was proposed as a marker of systemic inflammatory response and survival in patients with cirrhosis. OBJECTIVE: Evaluate the prognostic role of NLR in cirrhotic patients and its relation with inflammatory cytokines(IL-6, IL-10 and IL-17). METHODS: In this prospective study two groups were evaluated: 1) Stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Maccali et al also directly associated the NLR with the MELD score and other markers of disease severity, highlighting this parameter as an important predictor of adverse outcomes and mortality. In that study, the NLR was higher in patients with bacterial infections than those without bacterial infections (4.95 vs. 3.49) (25). In the study by Kwon et al (8), the NLR in liver cirrhosis patients with infections was significantly higher than in those without infections (8.3 vs. 4.9), acting to identify patients at risk of poor outcomes and predict 1-month survival.…”
Section: Discussionmentioning
confidence: 74%
“…Maccali et al also directly associated the NLR with the MELD score and other markers of disease severity, highlighting this parameter as an important predictor of adverse outcomes and mortality. In that study, the NLR was higher in patients with bacterial infections than those without bacterial infections (4.95 vs. 3.49) (25). In the study by Kwon et al (8), the NLR in liver cirrhosis patients with infections was significantly higher than in those without infections (8.3 vs. 4.9), acting to identify patients at risk of poor outcomes and predict 1-month survival.…”
Section: Discussionmentioning
confidence: 74%
“…First, during the initial stages of infections, the innate immune response dominates the host’s reaction. According to current knowledge, after the activation of pattern recognition molecules, the process follows a very similar pathway regardless of the response being triggered by DAMPs or PAMPs (inducing a similar set of response elements via activation of common, conserved early response pathways) [ 11 , 28 , 36 , 37 ]. The binding of DAMPs and PAMPs to pattern recognition molecules induces the release of inflammatory cytokines, acute-phase proteins, the formation of reactive oxygen and nitrogen species, the induction of antigen-presenting cells and, finally, the initiation of adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…In liver cirrhosis, NLR is expected to increase with disease progression, but there are insufficient data [ 10 ]. The value of NLR is influenced by ongoing infection, trauma, hemorrhage, etc., so, within a given Child–Turcotte–Pugh (CTP) stage, NLR is supposed to be higher in the presence of infection and associated with worse survival [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Kalra et al proved that high NLR can determine the risk for cirrhotic decompensation, independently of Model for End-Stage Liver Disease (MELD) score and stage of cirrhosis (Kalra et al, 2017). In similar fashion, Maccali et al concluded that the early identification of NLR increase, in the first 48 h of hospitalization, predicts short-term mortality for patients with acute decompensation of liver cirrhosiscaused by various etiologies, including NAFLD (Maccali et al, 2021).…”
Section: Characteristics Of Neutrophil Infiltration In Pediatric Non-...mentioning
confidence: 94%